Analysis of user behavior on the website of a university eye hospital in Germany. Issue 30 (24th July 2020) - Lang, Stefan J.; Böhringer, Daniel; Bach, Michael; Reinhard, Thomas
Abstract : Abstract: Medical information websites are usually targeted toward patients, physicians, and medical students. Most of the latest studies researched the usability of such websites. However, reports on user numbers and behavior are rare. The goal of our study is to analyze the utility of a website of a large tertiary referral center in ophthalmology in terms of various target audiences (patients, applicants, medical students, referring ophthalmologists). The web access data from our institutional website was assessed with Google Analytics. Data collection started in 2016. From 2016 to 2018, we counted a total of 763, 942 page views. The overall number of users dropped from 81, 572 to 67, 740. This drop's onset correlates with a change in the website structure. All target audience pages received constant traffic from 2016 to 2019, with the patients' and doctors' sites attracting the most traffic. The pages for medical students and job applicants, although not viewed often, revealed a long session duration. Our website is used by all our target audiences. The behavior and the user numbers of each target group differ. Changes to a website's structure can influence the number of users and their behavior. It is not possible to make a direct comparison to other institutions' websites as there are so few similar reports available. By adding more parameters to the analytics profile in a prospective setting, more detailed analyses of user behavior may be possible in the future.